2014
DOI: 10.1111/jmi.12113
|View full text |Cite
|
Sign up to set email alerts
|

Neural network modelling of asphalt adhesion determined by AFM

Abstract: SummaryThis study constructs a neural network (NN) model to quantify adhesion from atomic force microscopy (AFM) data. AFM data contain five-point force-distance values. A total of 760 observations are used to build NN model. To train the network, AFM tip-sample distance data, percentage of lime, type and percentage of polymer and asphalt chemical functional groups are given as inputs and AFM force as an output. To select the NN architecture, one and two hidden layers with varying neurons are tried with 10 inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Tarefder and Ahsan developed the MLP model to predict the adhesion forces of asphalts modified by different factors under nanoscale evaluation of asphalts by AFM. The obtained adhesive force from the model was very satisfactory [17]. It was also found that the adhesion force is significantly affected by asphalt chemistry.…”
Section: Previous Studies On Neural Network Modellingmentioning
confidence: 66%
“…Tarefder and Ahsan developed the MLP model to predict the adhesion forces of asphalts modified by different factors under nanoscale evaluation of asphalts by AFM. The obtained adhesive force from the model was very satisfactory [17]. It was also found that the adhesion force is significantly affected by asphalt chemistry.…”
Section: Previous Studies On Neural Network Modellingmentioning
confidence: 66%
“…And, indeed, some improvement in adhesion force was noticed at nanoscale where the sample studied was modified by some hydrocarbon additives that can be seen in Rebelo's study [22]. Also, Tarefder et al [56,57] found this adhesion force enhancement occurred, in general, when asphalt was modified with common styrene-butadiene (SB), SBS polymers, and limes.…”
Section: Adhessibility Of Asphalt Phasesmentioning
confidence: 78%
“…However, there was no drastic change in the error values which indicates that the model did not overfit the training samples. Different artificial intelligence (AI) techniques, such as multilayer perceptions (MLPs), support vector machines (SVMs), and adaptive network fuzzy inference systems (ANFISs), have been used for predicting adhesion force for asphalt [46]. However, for pavement design, these techniques cannot explain the relationship between the variables considered in the study, which makes the use of the proposed model in decision-making difficult.…”
Section: Resultsmentioning
confidence: 99%